Grace and the preacher [large type] : a novel - Sawyer, Kim Vogel (Thorndike Press, a part of Gale, Cengage Learning, 2017)
"At the age of twenty-four, postmistress Grace Cristler has all but given up hope of finding a husband among the narrowing group of eligible men in her town of Fairland, Kansas. But when her uncle decides to retire from the pulpit, Grace is responsible for corresponding with the new preacher set to take his place. She can't deny the affection growing in her heart for Reverend Rufus Dille-- a man she deeply admires, but has only met through his letters. Theophil Garrison is on the run from a past and a label he's desperate to escape. Ten years ago, his outlaw cousins convinced him to take part in a train robbery, but Theo fled the scene, leaving his cousins to face imprisonment. Now their sentence is complete, but the plan for vengeance has only just begun. Branded a coward and running for his life, a chance encounter could provide Theo with the escape he needs. But the young man's desperate con might come at an enormous price for the tenderhearted Grace-- and the entire town. Will Grace's undeserved affection and God's mercy make something beautiful from the ashes of Theo's past?"--Amazon.com